2021
DOI: 10.1016/j.arrct.2020.100095
|View full text |Cite
|
Sign up to set email alerts
|

mHealth Intervention Applications for Adults Living With the Effects of Stroke: A Scoping Review

Abstract: Objective To conduct a scoping review of mobile health (mHealth) application (app) interventions to support needs of adults living with the effects of stroke reported in the literature. Data Sources PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), and Scopus were systematically searched for peer-reviewed publications. Articles were published between January 2007 and September 2020 and met predefined inclusion and exclusion criteria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…A scoping review that evaluated mHealth for all phases of stroke care found that most studies were underpowered and were pilot and feasibility studies and case series (with no mHealth studies using stroke as a primary outcome). 27,28…”
Section: Primary Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…A scoping review that evaluated mHealth for all phases of stroke care found that most studies were underpowered and were pilot and feasibility studies and case series (with no mHealth studies using stroke as a primary outcome). 27,28…”
Section: Primary Preventionmentioning
confidence: 99%
“…A scoping review that evaluated mHealth for all phases of stroke care found that most studies were underpowered and were pilot and feasibility studies and case series (with no mHealth studies using stroke as a primary outcome). 27,28 The Stroke Riskometer is one of the few digital applications that has been scientifically evaluated and is endorsed by the World Stroke Organization and World Federation of Neurology. 29 The Stroke Riskometer derives from the Framingham stroke prediction algorithm with additional risk factors based on the INTERSTROKE study (eg, diet, non-White race, stress level, and alcohol consumption).…”
Section: Primary Preventionmentioning
confidence: 99%
“…An easily to implement and cost-efficient approach to support risk factor management, especially in younger patients with stroke might be mobile health (mHealth) (11)(12)(13). The mHealth is defined as the use of mobile and wireless technologies, such as smartphones and tablets, to support the achievement of health objectives.…”
Section: Introductionmentioning
confidence: 99%
“…Educational programs and dedicated workshops should be developed to inform the local healthcare professionals about the concept of level of evidence and clinical recommendations. The utilization of new affordable technologies (e.g., mHealth) may provide an alternative to the above-mentioned restrictions of rehabilitation or may supplement the present rehabilitation programs ( 13 ). mHealth has the potential to significantly benefit LMICs by overcoming a shortage of healthcare professionals, advancing rehabilitation, and reducing health inequalities through increased access to rehabilitation.…”
Section: Call For Action: the Development Of High-quality Scientific ...mentioning
confidence: 99%